2007
DOI: 10.1097/00004010-200701000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Health care work environments, employee satisfaction, and patient safety

Abstract: Patients and quality leaders continue to call for delivery of patient-centered care. If climates that facilitate such care are also related to improved patient safety and nurse satisfaction, proactive, patient-centered management of the work environment could result in improved patient, employee, and organizational outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 24 publications
4
113
0
4
Order By: Relevance
“…The reason for an individual to not report an error that he or she made, or which was made by someone close, is often a lack of trust that responsible managers in the organization will conduct proper analyses to determine the true causes. It is a common and simple solution for organizations to blame an error on an individual (Hofmann & Stetzer, 1998;Rathert & May, 2007). The belief that organizations prefer to blame individuals rather than to find organizational causes is supported by data: Perrow (1999) reported that a re-examination of industrial accident causes where 70% to 80% were attributed to operator errors, in contrast found that operators had caused less than half of the accidents they were blamed for, or that 30% to 40% of accidents were caused by operator errors.…”
Section: ) Lack Of Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for an individual to not report an error that he or she made, or which was made by someone close, is often a lack of trust that responsible managers in the organization will conduct proper analyses to determine the true causes. It is a common and simple solution for organizations to blame an error on an individual (Hofmann & Stetzer, 1998;Rathert & May, 2007). The belief that organizations prefer to blame individuals rather than to find organizational causes is supported by data: Perrow (1999) reported that a re-examination of industrial accident causes where 70% to 80% were attributed to operator errors, in contrast found that operators had caused less than half of the accidents they were blamed for, or that 30% to 40% of accidents were caused by operator errors.…”
Section: ) Lack Of Informationmentioning
confidence: 99%
“…In line with the tendency to blame the person who is closest to an error, factors that impede error reporting and analysis at the organizational level can be linked to the culture of blaming individuals rather than exploring other error causes , ward climate , whether health care work units are patient-centered (work is planned around the patient's needs) (Rathert & May, 2007) and that when greater distance between professional groups in health care reduces the willingness of orderlies and nurses to admit to or discuss errors with doctors ). Organizational climate is a determinant that trickles down to affect both group and individual-level learning from failure.…”
Section: Page 18 Of 72 Academy Of Management Annalsmentioning
confidence: 99%
See 2 more Smart Citations
“…[33] Other suggestions pertaining to structure include managers encouraging nurses to spend the time they need with patients and to encourage nurses to offer suggestions on how to improve work flow thereby, being able to spend time getting to know their patients. [49] More broadly, managers should be encouraged to account for variables in their environment they can change rather than focussing solely on organizational goals like patient satisfaction or revenue. [49] Focus on relationship building among nurses and patients can also be of benefit to health care administrators and hospital managers.…”
Section: Discussionmentioning
confidence: 99%